Pengaruh Kualitas Pelayanan terhadap Keputusan Pembelian Pengguna Bahan Bakar Minyak Pertamina di SPBU 14.201.180 - Nadya Rahmadhani; Sepania Tiarasi; Linsa Febby Br Barus; Vini Andayani Manik; Riyani Sijabat; Feby Caroline; Andika Sihotang; Daniel Martinus; Mukmin Siregar; Ivo Selvia Agusti (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of service quality on the purchasing decisions of fuel consumers at Pertamina Gas Station (SPBU) 14.201.180. In the increasingly competitive business environment, service quality has become a critical factor in shaping customer loyalty and purchase decisions. The research adopts a quantitative approach, utilizing questionnaires distributed to 200 respondents. Data were analyzed using simple linear regression, t-test, F-test, and the coefficient of determination with the help of SPSS 27 software. The findings indicate that service quality has a positive and significant effect on purchasing decisions. The regression analysis reveals that improvements in service quality contribute to a 27.7% increase in purchasing decisions. Therefore, enhancing aspects such as service timeliness, staff friendliness, facility cleanliness, and fuel quantity accuracy is essential for increasing customer satisfaction and loyalty at SPBU. The study recommends optimizing service through staff training, digital technology adoption, and the establishment of consistent service standards to maintain Pertamina’s competitiveness in the fuel retail market.